If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2 = x + 14 Reorder the terms: 2 + 4x = x + 14 Reorder the terms: 2 + 4x = 14 + x Solving 2 + 4x = 14 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + 4x + -1x = 14 + x + -1x Combine like terms: 4x + -1x = 3x 2 + 3x = 14 + x + -1x Combine like terms: x + -1x = 0 2 + 3x = 14 + 0 2 + 3x = 14 Add '-2' to each side of the equation. 2 + -2 + 3x = 14 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = 14 + -2 3x = 14 + -2 Combine like terms: 14 + -2 = 12 3x = 12 Divide each side by '3'. x = 4 Simplifying x = 4
| 8-7x=40-35x | | 4t^2+10=74 | | 5x+11=2x+20 | | r=5f+5s | | -11x-151=65+7x | | X-31=-56 | | 7m-2=19 | | 3(5x-2)=4(3x+3) | | x+0.67=0.83 | | 6x+13=-13-7x | | 2-(3-x)=7x+5-2x | | 3x/4-2.78=1.75 | | 2x+2(x+5)=58 | | 2-(3-x)=7x+5-2 | | 10x-15=6x+9 | | x-18=-34 | | 2x^2-32x+78=0 | | x-2.71=0.67 | | 4(3x+1)=-20 | | 25c^3-16c=0 | | B=p+3a+2c | | (b-2/15)=1 | | 6x-3x-9+1=5x+7x-3 | | 2+8v=-94 | | x^3+x^2-21x-45=0 | | 0.16x+27=28 | | 3(x+7)=6(x-1)-4 | | P=b+3a+2c | | 7y-3=6y+9 | | x/3-24=81 | | 5-2[5-(6y-2)]= | | -129-[7-8y-5(6y-2)]= |